Genome-Wide Analysis of WRKY Genes and Their Response to Salt Stress in the Wild Progenitor of Asian Cultivated Rice, Oryza rufipogon - Nan, Hong; Li, Wei; Lin, Yang-lei; Gao, Li-zhi (Frontiers in Genetics, 2020)
WRKY gene family is widespread in plants, which is of significance in determining plant development and stress response. Although WRKY transcription factors have been widely characterized in many plants, a genome-wide analysis of the WRKY gene family is still lacking in Oryza rufipogon. In this study, we identified 101 O. rufipogon WRKY (OrWRKY) transcription factors, which were further classified into eight subgroups. Phylogenetic analysis showed that OrWRKY transcription factors were supported by highly conserved motifs and gene structures. Chromosomal distribution of OrWRKYs indicated that most genes were dispersed on all twelve chromosomes, especially enriched on Chromosome 1. Syntenic analysis revealed that 69 (68.3%) genes were derived from either segmental (49) or tandem duplication events (20), suggesting a essential role of segmental duplications. We characterized a total of 39 orthologous gene pairs between O. sativa ssp. japonica WRKY (OsjWRKY) and OrWRKY. We then performed quantitative real-time polymerase chain reaction (qPCR) experiments to validate tissue-specific and differential expression of the OrWRKYs. We also investigated corresponsive expression of the OrWRKYs in response to salt stresses in leaves and roots. This study gains a new insight on the evolution of the OrWRKYs and will help further functional characterization of candidate genes towards wild rice germplasm exploration for rice genetic improvement.